The Role of Information Systems in Managing Student Report Card and Attendance Data in Junior High Schools - Santi Puspa Oktaviane; Novi Rukhviyanti (LPPM Institut Pendidikan Nusantara Global, 2026)
Administrative academic activities in many Junior High Schools are still carried out manually, such as entering student grades and attendance using separate worksheets. This process often leads to delays, data duplication, and calculation errors that affect the accuracy of report card results. To address these issues, this study aims to develop a web-based information system for managing student report card and attendance data that can integrate all academic processes digitally. The research employed a Research and Development (R&D) method, consisting of needs analysis, system design, prototype development, and implementation testing. The system was developed using PHP and MySQL with a user-centered design approach to ensure ease of use for teachers, homeroom teachers, and administrative staff. The findings indicate that the system successfully reduced the time needed for grade recap from seven days to three days and decreased input errors by more than sixty percent. User responses showed a high level of satisfaction regarding the system’s ease of use, speed, and accuracy. Therefore, this information system is effective in improving the efficiency, transparency, and accountability of managing report card and attendance data in Junior High Schools